Past bodies : body-centered research in archaeology - Borić, Dušan.; Robb, John, 1962 March 18- (Oxford, UK : Oxbow Books, 2008)
"This collection of papers is a reaction to decades of the body's invisibility in archaeology. It raises the body as the central topic in the study of past societies, researching its appearance in a wide variety of regional contexts and across vast spans of archaeological time. Contributions in this volume range from the deep Epi-Palaeolithic past of the Near East, through the European Neolithic and Bronze Age, Classical Greece and Late Medieval England, to pre-Columbian Central America, post-contact North America, and the most recent conflicts in the Balkans. In all these case studies, the materiality of the body is centre stage. Possibilities are highlighted for future study: by putting the body at the forefront of these archaeological studies an attempt is made to provoke the imagination and map out new territories."--BOOK JACKET.
Body theory in archaeology / Dušan Borić and John Robb -- The corporeal politics of being in the Neolithic / Douglass Bailey -- Changing beliefs in the human body in prehistoric Malta 5000-1500 BC / Simon Stoddart and Caroline Malone -- Idealism, the body and the beard in classical Greek art / Robin Osborne -- When the flesh is solid but the person is hollow inside : formal variation in hand-modelled figurines from Formative Mesoamerica / Rosemary Joyce -- Fractal bodies in the past and present / Chris Fowler -- From substantial bodies to the substance of bodies : analysis of the transition from inhumation to cremation during the Middle Bronze Age in Central Europe / Marie Louise Stig Sørensen and Katharina C. Rebay -- The extraordinary history of Oliver Cromwell's head / Sarah Tarlow -- Fresh scars on the body of archaeology : excavating mass-graves at Batajnica, Serbia / Slobodan Mitrović -- Meaningless violence and the lived body : the Huron-Jesuit collision of world orders / John Robb -- Bodily beliefs and agricultural beginnings in Western Asia : animal-human hybridity re-examined / Preston Miracle and Dušan Borić -- Is it 'me' or is it 'mine'? : the Mycenaean sword as a body-part / Lambros Malafouris -- Embodied persons and heroic kings in Late Classic Maya imagery / Susan D. Gillespie -- Colonised bodies, personal and social / Nan A. Rothschild -- The challenge of embodying archaeology / Chris Shilling.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Human remains (Archaeology); Human body -- Symbolic aspects; Human body -- Social aspects; Excavations (Archaeology); Restes humains (Archéologie); Corps humain -- Aspect symbolique; Corps humain -- Aspect social; Fouilles (Archéologie); SOCIAL SCIENCE / Archaeology; Excavations (Archaeology); Human body -- Social aspects; Human body -- Symbolic aspects; Human remains (Archaeology); Corps humain -- Aspect symbolique; Corps humain -- Aspect social; Fouilles archéologiques.; Mänskliga kvarlevor; Människokroppen -- attityder till -- historia